The Future of Voluntary Hospital Contributory Schemes - The point of view of the wage earning community / by H. H. Elvin - Elvin, Herbert Henry
1938-12-14 1938 1930s 7 pages Voluntary Hospital Contributory Schemes, WAGE EARNING COMMUNITY'S VIEW 5. family. The heroism of women in the Distressed and other Areas is not half appreciated. They will not only suffer discomfort but also risk their health rather than that those at home should suffer. Hours of waiting in an Out-Patients Department will not assist in such an undesirable state of affairs. Even some of those who do stick it, discover at the end of it that the doctor they wished and expected to see is not to be the one to attend to them. It is no use advocating free choice of doctors outside Hospitals if it is not practicable, in a minor degree, inside Hospitals. One of the remedies might be to endeavour to persuade more medical men to come in to deal with pressure of this sort. Speaking of doctors reminds me that Hospitals might be used as a means of giving Refresher Courses for doctors. A medical friend of mine insists upon going into "retreat" periodically. He tells me that by getting away from his practice he keeps fresh, keeps himself up-to-date, and his patients are all the better for it. Certainly he has a most successful practice, and, incidentally his periodical departures give an opportunity to "locums". It ought not, in my opinion, to be beyond the bounds of possibility for an arrangement to be come to between the B.M.A. and the Hospitals by which this could be done, to the benefit of all concerned. In this connection I should like to pay a tribute first to the medical staff, and secondly to the nursing staff of our Hospitals. The fine voluntary service of the medical practitioners is not always appreciated as much as it ought to be. No doubt they gain from their experience, but this should not be the reason why their services should not receive recognition. As to the Nurses, the term "God's Good Angels" is often used to cover poor pay and inferior conditions of service. It is marvellous to me that in spite of these conditions such fine service is rendered. The General Council of the Trades Union Congress is doing what it can for them, and I would put in a plea to all Hospital Authorities that they should consider the Charter we have drawn up. I believe that if this Charter were to be put into operation, not only would the patients be the gainers thereby, but that Hospitals themselves would benefit. I should like to see an effort made by which our Hospitals or Sub-Clinics are linked up with industry. Some of the big firms are able to have their own doctor, and I consider that it would be well if in industry some plan were adopted by which workpeople could be periodically medically examined, or able to go promptly to some medical man when feeling unwell. Illnesses are economically wasteful, and one of the reasons is that workers who ought to lay up, or even visit a doctor, will not do so because if they have to have time off for this purpose they are likely to lose their jobs, or at any rate a part of their income. 292/842/2/220